Real Earning Management Viewed from Financial Performance - Arum, Nurlita; Prasetyo Aji, Nur; Prasetyo Adi Utomo, Wisnu (Inovasi Analisis Data, 2024)
The aim of this research is to determine the relationship between the influence of profitability, company size and managerial ownership on real earnings management. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange BEI in 2020-2022. This research used a purposive sampling technique and obtained 53 companies, with an observation period of 3 years. The analytical tool used in this research uses multiple linear regression analysis. Data analysis begins with descriptive statistics, classical assumption testing, accuracy model testing, and hypothesis testing. The research results show that profitability and company size have a significant influence on real earnings management. Meanwhile, leverage and managerial ownership do not have a significant influence on real earnings management. The novelty in this research reveals the use of real earnings management practices which usually use accrual earnings management which can be a guide for practitioners and regulators in optimizing policies related to financial reporting.